Ocean shipping company's encroachment with outsourcing competition. (November 2022) - Zhang, Li-Hao; Zhang, Yang-Guang; Wang, Shan-Shan
Highlights: We analyze the interaction between upstream encroachment and service outsourcing. Forwarders are always worse off with the OS company's encroachment. Forwarders can deter upstream encroachment by improving cargo-canvassing capacity. The timing of OS company's encroachment is discussed. Introducing competing HS companies is always the optimal hinterland scheme. Abstract: As a new source to increase profits, some ocean shipping (OS) companies are beginning to encroach on the downstream market to canvass for cargoes, which would form a co-opetition relationship between OS companies and forwarders. Meanwhile, forwarders need to complete the transportation tasks through outsourcing strategy selection, that is, choose a delegation decision to outsource all transportation to an OS company, or choose a control decision to outsource ocean transportation and hinterland transportation to the OS and hinterland shipping (HS) companies, respectively. This paper uses a game-theoretical model to study the equilibrium strategy of OS company's encroachment and forwarders' outsourcing, and to further explore the strategic interactions between the two strategies. We solve the model analytically and find that an OS company might be worse off from encroaching on the shipping market if the entry cost is high or the cargo-canvassing capacity is high, whereas forwarders are always worse off with the OS company's encroachment. Surprisingly, forwarders can suppress the OS company's encroachment by changing their outsourcing decisions from control to delegation, or by improving their cargo-canvassing capacities. Our study also shows that forwarders prefer control decisions in the non-encroachment scenario, and they prefer delegation decisions if the market competition is fierce in the encroachment scenario. As for the HS scheme, introducing competing HS companies into hinterland transportation is always the optimal choice. Further, we consider an extension of the effect of OS company's encroachment timing and show that forwarders as the first movers can make the OS company be less possible to encroach on the shipping market.